Cancer cell signaling : methods and protocols - Terrian, David M (Humana Press, 2003)
East Carolina Univ., Greenville, NC. Text provides researchers with new strategies and procedures for investigating how the signaling cascades essential to normal cell life are corrupted, as well as developing new molecular tools for cancer therapy. Hardcover, e-book not yet available. DNLM: Neoplasms--physiopathology--Laboratory Manuals.
Methods in molecular biology ; Vol. 218
Keywords: Neoplasms; biologie; nádory; signální transdukce; patologie; Signal Transduction